Endoplasmic Reticulum Stress and miRNA Impairment in Aging and Age-Related Diseases - Demirel-Yalciner, Tugce; Sozen, Erdi; Ozer, Nesrin Kartal (Frontiers in Aging, 2022)
Aging is a physiological process defined by decreased cellular and tissue functions. Reduced capacity of protein degradation is one of the important hallmarks of aging that may lead misfolded protein accumulation and progressive loss of function in organ systems. Recognition of unfolded/misfolded protein aggregates via endoplasmic reticulum (ER) stress sensors activates an adaptive mechanism, unfolded protein response (UPR). Initial step of UPR is defined by chaperone enhancement, ribosomal translation suppression, and misfolded protein degradation, while prolonged ER stress triggers apoptosis. MicroRNAs (miRNAs) are non-coding RNAs, affecting various signaling pathways through degradation or translational inhibition of targeted mRNAs. Therefore, UPR and miRNA impairment in aging and age-related diseases is implicated in various studies. This review will highlight the recent insights in ER stress-miRNAs alterations during aging and age-related diseases, including metabolic, cardiovascular and neurodegenerative diseases, and several cancers.